The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1037/pas0000482
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of performance scoring in the d2 sustained-attention test: Cumulative-reliability functions and practical guidelines.

Abstract: We provide a psychometric analysis of commonly used performance indices of the d2 sustained-attention test, and give methodical guidelines and recommendations, based on this research. We examined experimental effects of repeated testing on performance speed and accuracy (omission and commission errors), and further evaluated aspects of test reliability by means of cumulative reliability function (CRF) analysis. These aspects were also examined for a number of alternative (yet commonly used) scoring techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
2
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(144 citation statements)
references
References 113 publications
(175 reference statements)
5
124
2
13
Order By: Relevance
“…Also, the correlation coefficients indicate that some of the TOVA measures are not sufficiently reliable, which is particularly true for the Response time variability score. This is consistent with other research; For example, a study found that the performance variability measures in the d2 attention test should be interpreted with caution as they lack reliability [16]. Another study demonstrated (by means of simulation analysis on grounds of classical test theory) that measures of performance variability can never achieve the same degree of reliability as compared to measures of central tendency (i.e., mean scores) [42].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, the correlation coefficients indicate that some of the TOVA measures are not sufficiently reliable, which is particularly true for the Response time variability score. This is consistent with other research; For example, a study found that the performance variability measures in the d2 attention test should be interpreted with caution as they lack reliability [16]. Another study demonstrated (by means of simulation analysis on grounds of classical test theory) that measures of performance variability can never achieve the same degree of reliability as compared to measures of central tendency (i.e., mean scores) [42].…”
Section: Discussionsupporting
confidence: 88%
“…To measure attention, we used the Test of Variables of Attention (TOVA) which has similarities with the d2 Sustained-Attention Test [16]. The TOVA is a computerized test measuring attention, that has been used to explore multiple health and developmental risks in the exploration of attention [1723].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy was studied and evaluated using commonly accepted tests [61][62][63] for perceived stress (PS), attention, concentration, and visual-scanning speed, and a computerized MT for the assessment of cognitive functions (learning, memory, and attention; for details, see Box A1 and Figure A3 in Appendix C).…”
Section: Ginsenosides Hrg80 (Mg/g *) Arkopharma (Mg/g) Placebomentioning
confidence: 99%
“…The d2 test of attention (Brickenkamp, 1962) is a widely used paper-and-pencil task measuring visual attention, concentration, and sustained attention (Bates & Lemay, 2004;Steinborn, Langner, Flehmig, & Huestegge, 2018). In this test, 14 lines of 46 characters in each line are presented to participants.…”
Section: Cognitive Measuresmentioning
confidence: 99%